Pengembangan komponen kompetensi kewargaan dalam buku teks Pendidikan Kewarganegaraan SMP/MTs - Arif, Dikdik Baehaqi (Universitas Negeri Yogyakarta, 2016)
This essay was aimed at describing the development of civic knowledge, civic skill and civic disposition on textbooks for junior high school namely